Constitutional and legal regulation of the staying of foreign citizens and stateless persons in the territory of the Republic of Kazakhstan as a means of suppression of illegal immigration - Вozhkarauly, А. (KSU publ, 2015)
The problem of migration is characterizing with special complexity, as it covers not only legal aspects, but also the problems of sociology, demograthy, political economy, ethnogeography, the problems of labor resources in the economics. The legal aspect have the special important place, because the migration is closely connected with the legal security, regulation and organization of migration processes, from which depends other problems of essential value for living conditions of the society.
Keywords: Migration; types of migration; labor migration; migration factors; international agreements; illegal migrationethnic migration; migration policy; concept of migration